Surgical interventions for type II superior labrum anterior posterior (SLAP) lesions - Chen, Dong (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects (benefits and harms) of different surgical techniques for treating type II superior labrum anterior posterior lesions.